Kaidah Marketing Berbasis Maqashid Al-Syari’ah Imam Al Ghazali - Sayuti, Mufit (Program Studi Ekonomi Syariah (ES) STAI Nahdlatul Ulama (STAINU) Malang, 2025)
Marketing in its development has always been the spearhead of a business's success, although from time to time, along with that there has also been a shift in the paradigm of consumer behavior as a marketing object. Marketing management based on maqasid sharia is a study, program, implementation, procedure and handling of processes that are built with the intention of realizing, forming and protecting commercial alterations with the target market with implications for conveying the direction of the organization by focusing on the level of sharia based on maslahah, balance and prioritizing the attitude of willingness and affection between sellers and buyers. The purpose of this study is to analyze the concept of marketing based on Imam Al-Ghazali's maqashid sharia which can be a guide for producers in marketing to consumers so that it is in line with the values of maslahat. This study focuses on the formulation of a marketing concept based on maqashid sharia according to Imam Al-Ghazali. This type of research is qualitative descriptive using a literature study approach. In the thoughts of Imam Al-Ghazali Ra regarding the concept of welfare, which mentions the five objectives of sharia or maqashid sharia, it can be used as a reference for economic actors, especially marketers, to be able to carry out their business process activities according to the rules of Allah SWT.